Natural compound-induced downregulation of antimicrobial resistance and biofilm-linked genes in wastewater Aeromonas species - Judan Cruz, Khristina G.; Takumi, Okamoto; Bongulto, Kenneth A.; Gandalera, Emmanuel E.; Kagia, Ngure; Watanabe, Kozo (Frontiers in Cellular and Infection Microbiology, 2024)
Addressing the global antimicrobial resistance (AMR) crisis requires a multifaceted innovative approach to mitigate impacts on public health, healthcare and economic systems. In the complex evolution of AMR, biofilms and the acquisition of antimicrobial resistance genes (ARGs) play a pivotal role. Aeromonas is a major AMR player that often forms biofilm, harbors ARGs and is frequently detected in wastewater. Existing wastewater treatment plants (WWTPs) do not have the capacity to totally eliminate antimicrobial-resistant bacteria favoring the evolution of ARGs in wastewater. Besides facilitating the emergence of AMR, biofilms contribute significantly to biofouling process within the activated sludge of WWTP bioreactors. This paper presents the inhibition of biofilm formation, the expression of biofilm-linked genes and ARGs by phytochemicals andrographolide, docosanol, lanosterol, quercetin, rutin and thymohydroquinone. Aeromonas species were isolated and purified from activated sludge samples. The ARGs were detected in the isolated Aeromonas species through PCR. Aeromonas biofilms were quantified following the application of biocompounds through the microtiter plate assay. qPCR analyses of related genes were done for confirmation. Findings showed that the natural compounds inhibited the formation of biofilms and reduced the expression of genes linked to biofilm production as well as ARGs in wastewater Aeromonas. This indicates the efficacy of these compounds in targeting and controlling both ARGs and biofilm formation, highlighting their potential as innovative solutions for combating antimicrobial resistance and biofouling.